A SYSTEMATIC REVIEW ON NANOCAPSULE: A NOVEL DRUG DELIVERY SYSTEM. - Karnakar, Bantu; Arvapalli, Swarupa; Jabeen, Syeda; A. Vaishnvi; Ps.Rishika; Sharma, J.V.C. (Journal of Biomedical and Pharmaceutical Research, 2021)
Nanocapsules, existing in miniscule size, which range from 10 nm to 1000 nm. They consist of a liquid/solid core in which the drug is placed into a cavity, which is surrounded by a distinctive polymer membrane made up of natural or synthetic polymers. They have great interest of attraction because of the protective coating, which are usually Pyrophoric and easily oxidized and delay the release of active ingredients.Various technical approaches are utilized for obtaining the Nanocapsules however, the methods of interfacial polymerization for monomer and the Nano deposition for preformed polymer are chiefly preferred. Most important characteristics in their preparation is particle size and size distribution which can be evaluated by using various techniques like X-ray diffraction, scanning electron microscopy, transmission electron microscopy, high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, superconducting quantum interference device, multi angle laser light scattering and other spectroscopic techniques.Nanocapsules possessing extremely high reproducibility have a broad range of life science applications. They may be applied in agrochemicals, genetic engineering, cosmetics, cleansing products, wastewater treatments, adhesive component applications, strategic delivery of the drug in tumors, nanocapsule bandages to fight infection, in radiotherapy and as liposomal nanocapsules in food science and agriculture.The enhanced delivery of bio-active molecules through the targeted delivery by means of a nanocapsule opens numerous challenges and opportunities for the research and future development of novel improved therapies.